Activity Based Costing for the better Supply Chain Management: An Integrated Approach for the Business Performance - Komalasari, Agrianti (International Journal of Supply Chain Management, 2018)
In the present business environment with the higher level of competition at world glance, supply chain management (SCM) helps the business firms to progressively improve their performance. For this purpose, the integration of cost management with the profitability is very much significant. For the proper SCM in the business, cost data with more accuracy and efficiency related to all the activities is much needed.  For the better business performance, activity-based costing or ABC approach has significantly contributed towards SCM.  In this context, the present study has been conducted to address the relationship between ABC and SCM from the context of various Indonesian business firms. For this purpose, various improvements which are offered by ABC to SCM for the business performance are examined.  By using the questionnaire approach, the current study is conducted regarding the SCM improvement with the organizational performance with the adoption of ABC. It is found that for the increasing performance through SCM, the adoption of ABC is much needed in the business firms.